Coping with Climate Change and Risk Management Strategies for Sustainable Rangeland-based Systems in WANA Region - Nefzaoui, Ali; Salem, Hichem Ben (Annals of Arid Zone, 2016)
Livestock is still the main source of income of rural populations in the West Asian and North African (WANA) countries. However, many factors including climate change are threatening the production systems. There are considerable gaps in our knowledge of how climate change will affect livestock systems and the livelihoods of these populations. Management of the production risk caused by the fluctuation of feed availability is the main problem hampering the development of livestock production in the WANA region. To overcome this situation governments emphasize different interventions, mainly subsidies, which are costly and use resources that could otherwise be spent for development purposes. This paper reviews some technical, institutional and policy options to help developing drought mitigation strategies. These options were developed and or evaluated in NARS and ICARDA over a decade under the framework of the Mashreq/Maghreb project targeting better integration of crop and livestock, community development and the improvement of the livelihoods of agropastoral communities in 8 countries of WANA. These options include (i) organization of local institutions to facilitate both collective and individual adaptation and response to climate change, (ii) an innovative approach to their sustainable improvement and management including institutional solutions for access to communal/collective rangelands, (iii) better use of local natural resources with an emphasis on water harvesting and appropriate use of adapted indigenous plant species, such as cactus and fodder shrubs, (iv) efficient animal feeding involving cost-effective alternative feeds like feed blocks and health monitoring, (v) the use of biotechnology as a potentially effective tool to breeding drought resistant forages and cereals and to biodiversity protection, (vi) development of early warning systems building on local knowledge, livelihood strategies and modern tools to forecast information on biophysical, economical, and markets environment to agropastoral communities. Success stories and difficulties faced when adopting these options are discussed. Key words: Climate change, rangeland, livestock, drought mitigation grazing, ruminants.